2011
DOI: 10.1371/journal.pone.0027878
|View full text |Cite
|
Sign up to set email alerts
|

miR-135A Regulates Preimplantation Embryo Development through Down-Regulation of E3 Ubiquitin Ligase Seven in Absentia Homolog 1A (SIAH1A) Expression

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNA molecules capable of regulating transcription and translation. Previously, a cluster of miRNAs that are specifically expressed in mouse zygotes but not in oocytes or other preimplantation stages embryos are identified by multiplex real-time polymerase chain reaction-based miRNA profiling. The functional role of one of these zygote-specific miRNAs, miR-135a, in preimplantation embryo development was investigated.Methodology/Principal FindingsMicroinjection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 56 publications
1
20
0
3
Order By: Relevance
“…The role of sperm-delivered miRNAs in the oocyte remains unclear because endogenous miRNAs have been shown to only poorly repress target mRNAs in the oocyte (Ma et al 2010 ). However, some studies have found that individual sperm-borne miRNAs, miR-135a and miR-34c, regulate key genes in the zygote and are crucial for normal embryo development (Pang et al 2011 ;Liu et al 2012 ). In addition, piRNAs are known to play a role in germ cell development, especially in the silencing of transposons by guiding DNAme (Aravin et al 2008 ;Law and Jacobsen 2010 ).…”
Section: Small Ncrnas In Spermmentioning
confidence: 99%
“…The role of sperm-delivered miRNAs in the oocyte remains unclear because endogenous miRNAs have been shown to only poorly repress target mRNAs in the oocyte (Ma et al 2010 ). However, some studies have found that individual sperm-borne miRNAs, miR-135a and miR-34c, regulate key genes in the zygote and are crucial for normal embryo development (Pang et al 2011 ;Liu et al 2012 ). In addition, piRNAs are known to play a role in germ cell development, especially in the silencing of transposons by guiding DNAme (Aravin et al 2008 ;Law and Jacobsen 2010 ).…”
Section: Small Ncrnas In Spermmentioning
confidence: 99%
“…As some miRNAs are stable, with a half-life of over 24 h (Winter and Diederichs, 2011), which is within the maturation time of a fertilized oocyte, it is conceivable that paternally derived miRNAs regulate translation immediately upon fertilization or at later stages of embryonic development. Accordingly, individual sperm-borne miRNAs, miR-135a and miR34c, have recently been shown to regulate key genes in the mouse zygote essential for normal embryonic development (Liu et al, 2012;Pang et al, 2011). Specifically, inhibition of miR-135a via microinjection of a synthetic antagomir reduced the percentage of zygotes developing to the two-cell stage (Pang et al, 2011).…”
Section: Small Ncrnas In Spermmentioning
confidence: 99%
“…Accordingly, individual sperm-borne miRNAs, miR-135a and miR34c, have recently been shown to regulate key genes in the mouse zygote essential for normal embryonic development (Liu et al, 2012;Pang et al, 2011). Specifically, inhibition of miR-135a via microinjection of a synthetic antagomir reduced the percentage of zygotes developing to the two-cell stage (Pang et al, 2011). This effect could be almost completely rescued by co-injection of an antibody against Siah1, a ubiquination/proteasome pathway protein, which is a direct target of miR-135a.…”
Section: Small Ncrnas In Spermmentioning
confidence: 99%
“…When miR135a is inhibited, first cell cleavage is suppressed. mir-135a regulates proteosomal degradation (Pang et al, 2011).…”
Section: Preimplantation Embryo Developmentmentioning
confidence: 99%